Hyperbolic volume and surface phonon polaritons excited in an ultrathin hyperbolic slab: connection of dispersion and topology. Issue 1 (2nd January 2021) - Wu, Xiaohu; Fu, Ceji
ABSTRACT: Hyperbolic volume and surface phonon polaritons have been studied extensively for enhancing the near-field radiative heat transfer (NFRHT) between hyperbolic materials. Hyperbolic volume phonon polaritons (HVPPs) describe propagating electromagnetic waves in hyperbolic materials while evanescent waves are required for excitation of hyperbolic surface phonon polaritons (HSPPs). Therefore, the dispersion relations of HVPPs and HSPPs are distinct. Here we study the interaction of HVPPs and HSPPs within the context of NFRHT between hyperbolic materials. We find that the dispersion curves of HVPPs and HSPPs in an ultrathin hyperbolic slab can connect smoothly. Particularly, we find that the topology of HVPPs can be convex and flat, rather than concave, and can be controlled by tuning the thickness of the hyperbolic slab, which has not been reported in published literature. We believe our findings presented here may help to deepen our understanding on the interaction between HVPPs and HSPPs, as well as the knowledge on the topology of HVPPs in hyperbolic materials.